(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Modern media are becoming an integral part of the system of social relations as a result of the development of science and technology. As a result of globalization, media are emerging not only as a means of disseminating or producing information, but also as a social institution that forms social consciousness, national values and traditions, patriotism and a sense of national identity in society. The research work comprehensively and theoretically analyzed social relations and their types, the impact of media on social relations. As a result, practical recommendations were developed on the basis of scientific approaches to develop the media space in society, increase the level of media literacy of the population, and create national media products. The research work can be used by students of higher education institutions, teachers and mentors, representatives of the field working in the field of journalism and media, and researchers conducting scientific research in the field of media and mass media.